Religious Moderation from The Viewpoint of Persaudaraan Alumni 212 - Maulana, Helmi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2024)
The objective of this study is to elucidate the phenomena of religious moderation based on the actual experiences of religious groups in terms of comprehension, expression, and moderation. The study focused on the Persaudaraan Alumni 212 in Ciamis West Java, which was selected as a representative example of various activities conducted within the context of religious political movements. The presence of these activities essentially constitutes a strategy of challenging individuals and religious factions in the public domain, therefore establishing a new dominant ideology known as populist Islam. The aims of this study are to investigate the conceptual comprehension of religious moderation, examine the notion of moderation as an epistemological and theological foundation in practical terms, and analyze the elements that influence behavior within the socio-political multicultural environment of the nation and state. This study employs qualitative research methods to examine interviews conducted with religious figures and ulama. The analysis is based on new social movement theories, religious authorities, contextual Islamic epistemology, and religious dialogue. The aim is to foster religious harmony in terms of thinking, application, and action/expression. The study findings suggest a significant correlation between the social, political, economic environment, religious organization affiliation, regional and national election political conditions, and the development of a religious moderation model in a certain jurisdiction. Moreover, the internet, social media, and electronic mass media offer extensive opportunity for accessing diverse religious information.